THE EFFECT OF BRAND VALUE CO-CREATION, BRAND TRUST, AND PERCEIVED EASE OF USE ON INVESTMENT INTEREST THROUGH ELECTRONIC WORD OF MOUTH : (Case Study On Landx Investors) - Janggih Maqsuda; Sopiah Sopiah; Agus Hermawan (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The contribution of MSMEs is large to the Indonesian economy, but this sector still has obstacles in obtaining capital. Therefore, referring to the Indonesian Capital Market regulations, the government through OJK (Financial Services Authority), issued Regulation Number 37/POJK.04/2018 on Crowdfunding Services through information technology-based stock offerings (Equity Crowdfunding). LandX is an ALUDI registered organizer that already has OJK license. The average level of funds raised by LandX per project is up to 4 billion. The population in this study are investors who have registered at LandX totaling 88,572 as of December 2022. Samples taken using purposive sampling. The conclusions of this study are Brand trust has a significant effect on investor interest in investing, Brand value co-creation engagement attitude has no significant effect on investor interest in investing in LandX through e-WOM, Brand value co-creation engagement behavior has a significant effect on investor interest in investing in LandX through e-WOM, Perceived ease of use has a significant effect on investor interest in investing in LandX through e-WOM and E-WOM has a significant effect on investor interest in investing in LandX.